Exchange rate dynamics and United States dollar denominated sovereign bond prices in emerging markets. - Hui, Cho Hoi (Metro Manila, Philippines Asian Development Bank, 2017)
The exchange rates of the currencies of Brazil, Colombia, Mexico, the Philippines, the Russian Federation, and Turkey can explain the pricing of these countries United States dollar denominated sovereign bonds, per empirical analysis. The relationship is particularly strong after the global financial crisis of 2008 to 2009. A two factor pricing model is developed with closed form solutions for the sovereign bonds. The correlated factors in the model foreign exchange rates and United States risk free interest rates follow a double square root process relevant in a low interest rate environment. The numerical results and associated error analysis show that the model credit spreads can broadly track market credit spreads.
Keywords: Finance -- Developing countries; Electronic books